Potrait Of Salafi Religion in Indonesia - Lubis, Sufrin Efendi; Pane, Riem Malini (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2024)
The diversity of religious sects in Indonesia requires maturity in attitude and action. In order for this diversity to make a positive contribution, the basic principles that overshadow all parties must be formulated, so that there is no assumption that what is in others is wrong while what is in ourselves and our group is the absolute truth. This research aims to describe the portrait of salafi religion in Indonesia. The research method used is a literature study. The author conducted studies from various sources ranging from historical records, previous journals and the latest mass media. All data obtained are then compiled and studied carefully to find the problems discussed. The results of this study show that the salafi generation in the modern era is quite unique and has a variety of styles. Although some of them reflect the ideology of the classical salaf generation, most of them do not reflect the way, nature and method of the salaf in interacting with religious issues, both in the nature of belief (akidah) and the rules (ibadah). In addition, there are also differences within the body of those who claim to be heirs of the salaf, which often reach the level of boycotting and even accusing them of being infidels. Although they look the same in appearance and dress, they differ in their references (idolized figures), addressing differences, tasamuh (level of tolerance) and other aspects both in principle and idhafi ta'abbudi (nuances of worship).